2023
DOI: 10.3390/molecules28237935
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Effects of Ginsenoside Rg2 and Rh1 on Nervous System and Related Mechanisms

Silu Liu,
Weijia Chen,
Yan Zhao
et al.

Abstract: Neurological-related disorders are diseases that affect the body’s neurons or peripheral nerve tissue, such as Parkinson’s disease (PD) and Alzheimer’s disease (AD). The development of neurological disorders can cause serious harm to the quality of life and functioning of the patient. The use of traditional therapeutic agents such as dopamine-promoting drugs, anticholinergic drugs, cholinesterase inhibitors, and NMDA receptor antagonists is often accompanied by a series of side effects such as drug resistance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“…For example, studies have shown that the ginsenosides Rd., Rg2 and Rh1 all have neuroprotective effects, and Rd. can reduce the neurotoxic effects of Aβ protein on C. elegans by resisting oxidative stress ( Mi et al, 2022 ), while ginsenosides Rg2 and Rh1 also have strong pharmacological activities in the nervous system, and can improve the body’s ability to resist neuronal damage, regulate neural activity, and can treat AD and vascular dementia ( Liu S. et al, 2023 ). Furthermore, Frondoside A, a saponin isolated from sea cucumber, can reduce the level of ROS in nematodes, decrease the oligomerization of Aβ proteins, and inhibit their toxicity ( Tangrodchanapong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have shown that the ginsenosides Rd., Rg2 and Rh1 all have neuroprotective effects, and Rd. can reduce the neurotoxic effects of Aβ protein on C. elegans by resisting oxidative stress ( Mi et al, 2022 ), while ginsenosides Rg2 and Rh1 also have strong pharmacological activities in the nervous system, and can improve the body’s ability to resist neuronal damage, regulate neural activity, and can treat AD and vascular dementia ( Liu S. et al, 2023 ). Furthermore, Frondoside A, a saponin isolated from sea cucumber, can reduce the level of ROS in nematodes, decrease the oligomerization of Aβ proteins, and inhibit their toxicity ( Tangrodchanapong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%